THE EFFECTS OF GLOBAL MONETARY POLICY ON FOREIGN DEBT AND DEBT CRISIS - Aničić, Dušan; Aničić, Jugoslav; Simić, Nataša; Bejatović, Gordana (Journal of process management and new technologies, 2019)
Economic policy of western developed countries is based on Washington agreement principles – liberalization, deregulation and privatization, with as little as possible participation of state in economic movements. Such policy is supported by the biggest financial institutions, from the World bank, IMF, US Federal Reserve, European banks and other. Although such policy gave a range of bad results in practice, its basic postulates are still in power. On the other hand, global economic crisis lead to the fact that many highly developed countries have problems of high foreign indebtedness. This problem is even more complex in countries in development and, so called, transitional countries, where Serbia belongs, which, by the relation of foreing debt towards GDP belogns to a group of countries with an intermediate debt, according to the World bank’s criteria.